Self‐assembly phenomena of the brush‐like amphiphilic organopolysiloxanes in aqueous solution. (6th August 2014) - Wu, Xu; Yu, Danfeng; Yang, Hui; Wang, Jinben; Liu, Zhaoqing; Su, Yuzhi
<x xml:space="preserve">Abstract</x> A series of brush‐like amphiphilic organopolysiloxanes with varying hydrophilic side‐chains was prepared, and the assembly behavior of these promising polymers was investigated in aqueous solution using a combination method of surface tension, steady‐state fluorescence, dynamic light scattering, and transmission electron microscopy. An increasing number of side‐chains could lead a higher surface tension of the polymer solution. The polymers formed regular "micelle‐like" spherical multipolymer assemblies in aqueous solution with the size distributed from the scale of hundreds to that of tens of nanometer, and the polymers that possessed more of the side‐chains would form comparatively loose and swollen assemblies with slightly higher micropolarities and bigger dimensions. The interesting discovery in this report was that the visible clearness of the solution could be improved by increasing the hydrophilicity of the assemblies in the solution. Copyright © 2014 John Wiley & Sons, Ltd.